Narrative factuality: a handbook - Fludernik, Monika; Ryan, Marie-Laure (Revisionen, 2020)
The study of narrative - the object of the rapidly growing discipline of narratology - has been traditionally concerned with the fictional narratives of literature, such as novels or short stories. But narrative is a transdisciplinary and transmedial concept whose manifestations encompass both the fictional and the factual. In this volume, which provides a companion piece to Tobias Klauk and Tilmann Köppe’s Fiktionalität: Ein interdisziplinäres Handbuch, the use of narrative to convey true and reliable information is systematically explored across media, cultures and disciplines, as well as in its narratological, stylistic, philosophical, and rhetorical dimensions. At a time when the notion of truth has come under attack, it is imperative to reaffirm the commitment to facts of certain types of narrative, and to examine critically the foundations of this commitment. But because it takes a background for a figure to emerge clearly, this book will also explore nonfactual types of narratives, thereby providing insights into the nature of narrative fiction that could not be reached from the narrowly literary perspective of early narratology.
Keywords: Aufsatzsammlung; Narrativität